Calcul Technologique, Cinétique et Modélisation du Platforming Catalytique RAZ - BERDAA HANANE (My University, 2011)
The objective of this study is to develop a complete mathematical model for simulation and optimization of catalytic reforming process. The model is developed from a base of fundamentalchemistry. Catalytic reforming is a refining process in which the major Gasoline quality is much improved gasoline quality is much improved. The main objective of the process is the transformation of hydrocarbons at low NO (octane) of gasoline with 50-60 octane high 90-105. This is achieved by converting naphtens to paraffins and isoparaffins and aromatics. Reforming is also an important source of hydrogen for other refinery processes. The process is usually done on a bi-functional catalyst (metal / acid). Modeling of catalytic reforming process allows us to take into account the main chemical reactions that occur in each reactor of the process and consider them in all aspects of technology, ie variation of operating parameters required such as temperature, pressure, space velocity: Hydrogen circulation rate in simulated adequate which will lead us to obtain a good quality gasoline (high octane) and secondly predict and prevent coking of the catalyst intens by beating the hydrocracking reactions.